Analysis of Language Vitality in Mongondownese English Education Students: A Language Policy Study - Nabu, Andiani Rezkita (English Education Department, 2024)
Several regional languages spoken in the province of North Sulawesi are listed as endangered, including the Mongondow language. Nonetheless, Mongondownese who have learned English find themselves in a difficult situation because they are expected to become fluent in English without losing their native tongue skills. Therefore, the purpose of this research is to describe the conditions of usage of the Mongondownese English Education pupils, the causes of conditions, as well as the policies and appropriate solutions to this problem. This qualitative study discovered numerous alternatives can be used, including policies pertaining to the educational sector, documentation and research, community involvement, institutional assistance, and political and legal policies.